Assessing Toxic Levels in Facial Creams from Burung-Burung Traditional Market, Gowa - Salnus, Subakir (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Facial cream is a skin care product that is widely used to improve appearance and overcome various skin problems. However, some unregistered products, especially those sold in traditional markets, can contain hazardous materials such as mercury. This study aims to identify the presence and levels of mercury in unregistered facial whitening creams sold in the Burung-Burung Traditional Market, Pattallassang District, Gowa Regency. Samples were analyzed using the Atomic Absorption Spectrophotometry (AAS) method. The results showed that five of the eight samples contained mercury exceeding the threshold set by BPOM RI, which is 1 mg/kg. This finding emphasizes the need for stricter regulation and supervision of cosmetic products to protect public health.